2021
DOI: 10.3390/ijms22062863
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Expression of Metabotropic Glutamate Receptor Subtype 5 in Idiopathic Autism Spectrum Disorder and Fragile X Syndrome: A Pilot Study

Abstract: Multiple lines of evidence suggest that dysfunction of the metabotropic glutamate receptor subtype 5 (mGluR5) plays a role in the pathogenesis of autism spectrum disorder (ASD). Yet animal and human investigations of mGluR5 expression provide conflicting findings about the nature of dysregulation of cerebral mGluR5 pathways in subtypes of ASD. The demonstration of reduced mGluR5 expression throughout the living brains of men with fragile X syndrome (FXS), the most common known single-gene cause of ASD, provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 44 publications
3
33
0
1
Order By: Relevance
“…Importantly, this difference in BP ND between the subjects with FXS and control group was significant in areas consistent with known distribution of mGluR5, and which have been functionally implicated in FXS symptomatology. Our results of overall reduced mGlu5 receptor expression in relevant regions of the brain in individuals with FXS replicate recent findings 17 and advance ongoing efforts for a much-needed measure of mGluR5 target engagement for drugs and treatment of symptoms in clinical trials of FXS and related disorders 36 , 37 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Importantly, this difference in BP ND between the subjects with FXS and control group was significant in areas consistent with known distribution of mGluR5, and which have been functionally implicated in FXS symptomatology. Our results of overall reduced mGlu5 receptor expression in relevant regions of the brain in individuals with FXS replicate recent findings 17 and advance ongoing efforts for a much-needed measure of mGluR5 target engagement for drugs and treatment of symptoms in clinical trials of FXS and related disorders 36 , 37 .…”
Section: Discussionsupporting
confidence: 84%
“…However, given the high co-morbidity of FXS and ASD 43 , the use of [ 18 F]FPEB to examine differences in mGluR5 binding potential between these disorder groups could significantly contribute to our understanding of the differences in underlying pathophysiology of the disorders; towards development of mechanism-based novel therapeutics in neurodevelopmental disorders. In one such study, Brašić and colleagues 37 , using [ 18 F]FPEB, replicated their earlier findings with FXS; but found that compared to subjects with typical development (TD), individuals with autism spectrum disorder (ASD) had higher mGluR5 expression in cortical areas and no difference in subcortical regions. The participants with ASD were younger than the controls.…”
Section: Discussionmentioning
confidence: 75%
“…Quantification of key receptor expression in the living human brain of men with FXS is also needed to better understand the results of failed FXS clinical studies and to continue to optimize FXS clinical study designs. This measurement may constitute an effective tool to confirm target engagement, for example of NAMs for mGluR5s, in both FXS and ASD (Brašić et al, 2020;Brašić et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Proper brain functioning requires precise development of neuronal circuits and network activation (Power et al., 2010; Tau & Peterson, 2010). Deficits in activation and synchronization of brain areas involved in communication and social interaction are well documented in ASD (Just et al., ,2004, 2007; Schipul et al., 2011), and neuroimaging studies show atypical activation patterns of brain regions related to the core ASD symptoms (Brašić et al, 2021; Dichter et al., 2009; Gilbert et al., 2008; Just et al., 2004; Kennedy et al., 2006; Di Martino et al., 2009; Schmitz et al., 2008). No consensus has been reached yet on glucose metabolism in individuals with ASD, as some FDG studies have shown no differences (Herold et al., 1988; De Volder et al., 1987) while others have reported either hypermetabolism (Rumsey et al., 1985) or hypometabolism (Haznedar et al., ,2000, 2006).…”
Section: Discussionmentioning
confidence: 99%